Väikeriigi bilateraalse arengukoostöö motiividest julgeolekupoliitilises kontekstis Eesti ja Soome näitel - Einre, Henrik (Tartu Ülikool, 2011)
This master’s thesis compares some of the main differences which rise from the comparison of security political discourses of Estonia and Finland. Specifically, certain aspects which concern the importance of development policy and cooperation within or connected to the security political discourses of the respective countries are compared. The difference which gave reason to write this thesis is to do with the choice of recipient countries of Estonia and Finland. These two states are in very close proximity to each other and are situated in the same geopolitical region, facing a shared potential source of threat. Despite of that, their choice of bilateral cooperation partners is very different. Finland has already a long tradition of giving foreign aid to certain African, Asian and South-American countries, while Estonia’s development aid is directed to former Eastern bloc countries such as the Ukraine, Georgia and Belarus among others. The significant difference in the list of recipient countries for foreign aid gave reason to investigate the motives behind the decisions to choose these particular countries. The first chapter of this thesis introduces different theoretical approaches which, describe the motives of development cooperation and securitization. Also different theories from the field of international relations are explained in order to strengthen the theoretical base. Among others more attention is paid to neorealist and (social-) constructivist influences. In addition to these also the differences of small and large states, specifically their security political behaviour is highlighted. Some newer and relevant theoretical connections between security and development are introduced in the second half of this chapter in order to emphasise the close connection between these two fields of investigation. One of these connections has been named „security development nexus“(SDN) and has influenced scientific approaches which analyze these two subjects concurrently since the beginning of the 21st century, hence it is a rather new approach. In the second chapter one introduces the methodological tool that is used to analyze the cases of Estonia and Finland. The methodological tool is discourse analysis, namely critical discourse analysis (CDA) with a focus on the formation and construction of official political discourses. Discourse analysis was chosen because it does not merely focus on the construction of texts but it forms a bridge between texts and their social context. CDA was also seen as an appropriate method because one of its purposes is to highlight the connections between language and power or the use of language in power relations. In the end of the theoretical part of this paper, three research questions are constructed. Two of the questions are set to find out country specific models of discursive characteristics for both Estonia and Finland. The third question is more analytical and by comparing the different discursive nuances tries to look behind the reasons why the discourses of Estonia and Finland are relatively different. In the last two empirical chapters of this thesis CDA is applied to the cases of Estonia and Finland to reveal the interdiscursivity or the shared parts of the security and cooperation-political discourses. The texts that are analyzed for these purposes include white papers or official security policy documents; official regulatory documents of development policy and official press releases from foreign and defence ministries over the period of 1998-2011. This period includes several changes in the respective discourses mostly because of global events which have brought along discursive changes. These kinds of events include the aftershocks of 9/11 and the war between Russia and Georgia in 2008; some references are also made to the global economic recession which started in 2008. The analysis and comparison of the official texts reveals that the security political discourses of Estonia and Finland are built on relatively different grounds. The Finnish discourse is based on the self-contained capability of guaranteeing the security of Finland while being a relatively neutral country which is not even a member of NATO and is mostly concerned with regional stability. Estonia, on the contrary, has tried to integrate into almost every European and North-Atlantic security and economic organization with the purpose of finding allies and stronger partners who would help to guarantee its security in case it is needed. A shared theme in the security political discourses of both countries is definitely Russia. Explicitly Russia is usually depicted as a somewhat unstable neighbour whose actions need to be under close attention but it is not described as an immediate source of threat. Implicitly, both Estonia and Finland see Russia as a dangerous source of multiple risks, ranging from political influences to military threats. Estonia’s discourse concerning Russia is more explicit, harsher and more straightforward than that of Finland, where Russia is seen definitely as a source of threats but it is not so clearly expressed. Due to these differences development cooperation also has a different role to play in the cases of Estonia and Finland. The analysis shows that in the Estonian case, development cooperation is subordinated to the security political discourse and is quite directly used as a tool to assure the security of Estonia. The motives behind this kind of construction of the security political discourse include sharing the values with global allies, strengthening weaker allies and parrying potential threats. The proof for this stems from the choice of recipient countries and also specific fields and projects into which the aid is directed, which tend to have quite a close connection with the security of the recipient country. One important pattern that becomes apparent through the comparison of these two countries is the flexibility and reaction speed to international events that could cause shifts in the security discourse. For example Estonia saw cyber and energy risks as potential threats to security already years before Finland, and proof for that can be found in the official documents. In the Finnish case, development cooperation stands apart from the security political discourse and its main motives are aimed at fulfilling the Millennium Development Goals (MDG) and providing an efficient soil for investments in the recipient countries. The choice of recipient countries and specific projects no doubt supports that claim because most of the recipient countries where Finnish aid is directed are situated in Africa and are even geographically too far for Finland to have any security interests in them. http://tartu.ester.ee/record=b2590596~S1